Didactic-pedagogical practices in remote teaching: challenges and possibilities in the Degree in Theater (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article aims to problematize the teaching-learning process in view of the limitations and possibilities that remote teaching offers us. We present the didactic-pedagogical choices developed for the disciplines of History of the Brazilian Theater I and III, of the Theater Degree at a public Brazilian university. From a questionnaire applied to both classes, it was possible to understand the dimension and effectiveness of the practices developed in line with the needs and profile of the classes. It is hoped that the discussions fostered can contribute to reflections on the quality of education at the present time, especially with regard to training in Higher Education.
Keywords: Remote education; Pandemic; Theater; Didactic-pedagogical practices; University education